Characteristics of factors, which worsen the clinical course and disturb the quality of life in patients with the combined pathology of asthma and chronic obstructive disease - Feschenko, Yuriy; Iashyna, Liudmyla; Nazarenko, Ksenia; Opimakh, Svitlana (ScienceRise: Medical Science, 2017)
The article studies factors that complicate the clinical course and disturb the life quality of patients with the chronic bronchial-obstructive pathology. Aim. To study factors that complicate the clinical course and disturb the life quality of patients with ACC for their rational modification. Materials and methods. All patients underwent: collection of anamnesis and general clinical examination, evaluation of the function of external respiration, clinical symptoms and risks. Results. At this work there were found factors that complicate the clinical course and life quality of patients with combined bronchial-obstructive pathology, especially clinical ones, such as expressed short breath, decrease of tolerance to physical loads and functional parameters of the external respiration. Conclusions of this work correspond to introduced recommendations as to the treatment of patients with ACC: effective anti-inflammatory and broncholytic therapy with the special accent on timely detection and adequate treatment of a concomitant pathology